10.2: Invited Paper: Development Prospect of Micro‐OLED Display Drive Technology. (28th November 2018) - Li, Shouxin
Abstract : This article mainly introduces the development and current situation of the driving technology of Micro‐OLED Displays, and analyzes the technical characteristics and the trends of future Micro‐OLED driving in combination with the market demand. According to the application of the AR / VR for High‐Resolution, High PPI, High Brightness Micro‐OLED Displays, Focus on introducing the advancing technologies that innovated by GoldenSi Tech company such as the UHR high resolution technology, Digital‐Analog Hybrid driving technology, HRR(High Refresh Rate) and DSF(Dynamic Sub‐field Drive) technologies, image processing and image quality optimization technologies, and propose a chip design architecture that meets the requirements of the next generation of Micro‐OLED/MicroLED Display drivers.